Analytical Estimates of Proton Acceleration in Laser-produced Turbulent Plasmas - Beyer, Konstantin (Cranfield University, 2018)
Poster presented at the 2018 Defence and Security Doctoral Symposium.With the advent of high power lasers, new opportunities have opened up for simulating astrophysical processes in the laboratory. We show that 2nd-order Fermi acceleration can be directly investigated at the National Ignition Facility, Livermore. This requires measuring the momentum-space diffusion of 3 MeV protons produced within a turbulent plasma generated by a laser. Treating Fermi acceleration as a biased diffusion process, we show analytically that a measurable broadening of the initial proton distribution is then expected for particles exiting the plasma.
Keywords: 'Cosmic-rays'; 'Fermi acceleration'; 'DSDS18 poster'; 'DSDS18'; 'Astrophysics'